2021
DOI: 10.31004/edukatif.v3i6.1522
|View full text |Cite
|
Sign up to set email alerts
|

Membangun Inovasi Organisasi: Antara Kepemimpinan Transformasional dan Proses Manajemen Pengetahuan

Abstract: Faktor kelemahan praktik leadership dan learning disebutkan sebagai di antara faktor penghambat kinerja inovasi organisasi. Mengingat masalah ini, penelitian ini mencoba untuk menyelidiki praktik dan efek kepemimpinan transformasional terhadap proses manajemen pengetahuan, dan juga pengaruh implementasi proses manajemen pengetahuan (dengan dimensi knowledge acquisition, knowledge dissemination, dan knowledge application) terhadap kinerja inovasi di industry manufaktur. Pendekatan Partial Least Square (PLS) dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
0
0
1
Order By: Relevance
“…Of the three dimensions, it is the administrative innovation dimension that has the highest contribution to the Makassar City Library Service. This finding strengthens the research conducted by (Hutagalung et al, 2021) that innovation in the organization needs to be done first to make changes and improvements which are the managerial aspects. When this can run well then other innovations will be easier to do, and this administrative innovation is the basis for other innovations.…”
Section: Discussionsupporting
confidence: 85%
“…Of the three dimensions, it is the administrative innovation dimension that has the highest contribution to the Makassar City Library Service. This finding strengthens the research conducted by (Hutagalung et al, 2021) that innovation in the organization needs to be done first to make changes and improvements which are the managerial aspects. When this can run well then other innovations will be easier to do, and this administrative innovation is the basis for other innovations.…”
Section: Discussionsupporting
confidence: 85%
“…Research Objects 7. (Sagala, 2020) The three basic components of customer-related information in the basic conceptual framework must be implemented in all organizations to offer great opportunities to organizations or companies (Hutagalung, 2021) In this study, it was found that of the three dimensions of the knowledge management process, only the application of knowledge has a significant effect on an organization's innovative performance.…”
Section: Differences In Variable Andmentioning
confidence: 91%
“…Karyawan yang inovatif menarik bagi pasar kerja dan tidak takut akan keamanan pekerjaan mereka karena daya tarik mereka yang tinggi dan mereka percaya bahwa pekerjaan baru mudah ditemukan jika diperlukan. Di sisi lain, karyawan yang tidak inovatif menganggap inovasi sebagai ancaman (Hutagalung et al, 2021;, dan inisiatif inovatif baru yang diperkenalkan oleh rekan kerja dianggap mengurangi keamanan kerja mereka sendiri. Lingkungan yang dicirikan oleh kepercayaan inovasi akan memungkinkan karyawan untuk memperkenalkan ide-ide baru karena mengetahui bahwa rekan kerja akan merespons secara positif.…”
unclassified